2014
DOI: 10.1111/brv.12114
|View full text |Cite
|
Sign up to set email alerts
|

Kdo2‐lipid A: structural diversity and impact on immunopharmacology

Abstract: 3-deoxy-d-manno-octulosonic acid-lipid A (Kdo2-lipid A) is the essential component of lipopolysaccharide in most Gram-negative bacteria and the minimal structural component to sustain bacterial viability. It serves as the active component of lipopolysaccharide to stimulate potent host immune responses through the complex of Toll-like-receptor 4 (TLR4) and myeloid differentiation protein 2. The entire biosynthetic pathway of Escherichia coli Kdo2-lipid A has been elucidated and the nine enzymes of the pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 180 publications
(247 reference statements)
0
86
0
Order By: Relevance
“…At that point, the lipid A s mixture was successively precipitated from the LPS by hydrolysis with 1% acetic acid for 2 h at 100 °C and purified by chromatography using Sephadex G‐50 and Sephadex G‐15 (Sigma‐Aldrich, St. Louis, MO. USA) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At that point, the lipid A s mixture was successively precipitated from the LPS by hydrolysis with 1% acetic acid for 2 h at 100 °C and purified by chromatography using Sephadex G‐50 and Sephadex G‐15 (Sigma‐Aldrich, St. Louis, MO. USA) …”
Section: Methodsmentioning
confidence: 99%
“…It is vital to mention that during the acid hydrolysis step, possible chemical degradation occurs, enhancing the risk of losing acid labile functional groups and the production of artifacts, thus resulting in the heterogeneity of lipid A . In addition, this heterogeneity may result from under‐acylation due to incomplete biosynthesis of the LPS . Although lipid A fatty acids usually contain 10 to 16 carbon atom chains, it has been shown that other unusual carbon chains such as C‐20 can exist within some isolates .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] Consequently,d evelopment of approaches for inhibitiono ft he LPS-inducedT LR4 activation hasb een af ocus of academic and pharmaceuticalr esearchi nt he past two decades. [14,15] It was unequivocally shown that down-regulation of TLR4-mediated signaling is beneficial for treatment of chronic and acute inflammation-related conditions including arthritis, [16] asthma, [17] neuroinflammation, [18] viral respiratory infection, [19] influenza [20] and sepsis [12,15,[21][22][23] Quite av arietyo fd ifferent tactics have been suggested for the inhibition of the deleteriousi nnate immune responses induced by LPS, which include deactivation of LPS by cationic antimicrobialp eptides; [24][25][26] intervention with the LPS transfer cascade involving LBP (LPS-binding protein) and CD14 (cluster of differentiation 14) [27][28][29][30] including development of TLR4 neutralizing antibodies. [31,32] Several innovative molecules with no similarity to Lipid Ah ave been proposed as candidates for blocking LPStriggered pro-inflammatory signaling.…”
Section: Introductionmentioning
confidence: 99%
“…It provides the anchor that secures the molecule within the membrane, while the polysaccharide component interacts with the external environment, including the defence of the animal or plant host species. The lipid A component is the primary immune‐stimulatory centre of LPS and is considered the most toxic part within the LPS biomolecule …”
Section: Introductionmentioning
confidence: 99%